Embodied Dependencies and Freedoms: Artistic Communities and Patronage in Asia - Hegewald, Julia A. B. (Dependency and Slavery Studies, 2023)
Most people regard the arts as free. This publication demonstrates that Asian art and architecture are created in contexts of extreme dependence. They depend on the climate, resources, social and religious traditions and patrons. Despite these asymmetrical dependencies, artists have found freedoms for self-expression. This creative dialogue is explored in 13 chapters on material culture from India, Nepal, Tibet, the Silk Routes and China